How Customer Referral Programs Turn Social Capital into Economic Capital. (February 2018) - Van Den Bulte, Christophe; Bayer, Emanuel; Skiera, Bernd; Schmitt, Philipp
Customers acquired through a referral program have been observed to exhibit higher margins and lower churn than customers acquired through other means. Theory suggests two likely mechanisms for this phenomenon: (1) better matching between referred customers and the firm and (2) social enrichment by the referrer. The present study is the first to provide evidence of these two mechanisms in a customer referral program. Consistent with the theory that better matching affects contribution margins, (1) referrer–referral dyads exhibit shared unobservables in customer contribution margins, (2) referrers with more extensive experience bring in higher-margin referrals, and (3) this association between the referrer's experience and margin gap becomes smaller over the referral's lifetime. Consistent with the theory that social enrichment affects retention, referrals exhibit lower churn only as long as their referrer has not churned. These findings indicate that better matching and social enrichment are two mechanisms through which firms can leverage their customers' networks to gain new customers with higher customer lifetime value and convert social capital into economic capital. One recommendation for the managers of the firm studied is to recruit referrers among their customers who have been acquired at least six months ago, exhibit high margins, and are unlikely to churn.